Development of CRISPR/Cas9-based tools and strains to improve the Sterile Insect Technique in the Mediterranean fruit fly, Ceratitis capitata - Aumann, Roswitha A.; Justus Liebig University Giessen (My University, 2021)
The mass release of male sterilized insects, which leads to infertile matings and, consequently, to reduce an insect population, is the basis of the ‘Sterile Insect Technique’ (SIT) for pest control. Although the SIT has been used successfully since the 1950s, some key aspects need to be further improved and still established in most pest insects. For example, the cost-effective separation of males and females for generating a 100% male population, the so-called sexing, which is a key technology for the success of the SIT. New targeted methods such as CRISPR/Cas facilitate the development of genetically modified insects that enable the application or optimization of SIT programs for economically important pest species. In this work, I present three studies that have significantly expanded the CRISPR/Cas genome editing and its applications in one of the most important pests, the Mediterranean fruit fly C. capitata. In the first study, I established sequence-specific, homology-directed repair (HDR) using CRISPR/Cas9 with an efficiency of up to 90%. This process was the world's first HDR process in Tephritids, and the high efficiency was essential for the other projects in this work. In the second study, all-male populations should be generated by manipulating sexual development. For this purpose, a temperature-sensitive variant of the Drosophila melanogaster sex determination gene transformer-2 was targeted in the homologous gene in C. capitata by CRISPR/Cas9 HDR. The resulting progeny were exclusively male. Due to the permissive temperature range of this mutation in C. capitata, the conditional control of the gender conversion was not possible. In the third study, the molecular puzzle around the white pupae gene of medfly was solved. The phenotype has been used in Genetic Sexing Strains (GSS) for decades, but without the knowledge on the genotype. Through extensive genome sequencing and functional CRISPR/Cas9 knock-outs in the Mediterranean fruit fly, we were able to verify a metabolite transporter encoding gene as causal for the white pupal shell. This now allows the white pupae phenotype to be constructed in other species. The results of this work are essential steps towards establishing a more universal approach to the development of GSS and optimizing SIT programs with CRISPR/Cas9 targeted mutagenesis without the use of transgenes – an approach in which the emerging strains are not classified as genetically modified organisms in many countries.
Keywords: CRISPR/Cas9; Sterile Insect Technique SIT; Ceratitis capitata; Insect Biotechnology; ddc:500; ddc:570; ddc:630